Movers or Stayers? Heterogeneity of Older Adults’ Residential Profiles Across Continental Europe - Fernández-Carro, Celia (European Spatial Research and Policy, 2012)
Traditionally, the emotional attachment older adults have to their homes and the economic and health burden caused by residential moves have had a deterrent effect on mobility during old age. In spite of this static general trend, 20% of older Europeans change their residential location after the age of 65. Some studies point out that this percentage will increase in the coming decades along with the onset of baby-boom cohorts reaching older ages. The main objective of this article is to describe the residential mobility trends during old age in some European countries and identify the main features of those elderly that move after 65, using data from the Survey of Health, Ageing and Retirement in Europe (SHARE).